La lectura pictográfica en el proceso de enseñanza aprendizaje en los niños y niñas de Educación Básica, (Preparatoria) en la Unidad Educativa Victoria Vásconez Cuvi-Simón Bolívar-Elvira Ortega, Latacunga. - Borja Padilla, Tania Margarita (2020)
In the present work, strengths and weaknesses in reading were identified, which will allow, through pictography, to improve the teaching-learning process, in children of the first year of basic education, for this reason it aims to motivate them to read; methodological strategies were made to develop reading using a mobile application; In the research, the quantitative approach was used with the deductive method based on the existing theories, it worked with the two variables, testing the theory in reality and statistically describing or predicting facts, obtaining quantitative and quantifiable data, by carefully examining the proposal, believes that the content is creative, original and innovator, easy to understand for teachers and children, it allowed to get involved in a very successful and dynamic way in the world of ICTs, giving them the opportunity to acquire new knowledge and strengthen comprehensive development, by incorporating two areas such as technology and teaching; In order to form the user manual, many strategies were used to achieve the objectives and a work with theoretical bases that will allow addressing the theme, the culture of Latacunga, such as the main characters of the Black Mama in September, for this reason considers that the proposal is dynamic and can easily reach the student, the use of the mobile application and the pictography is an advantage for the teaching-learning process.